Boron Separation Processes. - Kabay, Nalan; Bryjak, Marek; Hilal, Nidal (Amsterdam, Netherlands : Elsevier Ltd., 2015)
The impending crisis posed by water stress and poor sanitation represents one of greatest human challenges for the 21st century, and membrane technology has emerged as a serious contender to confront the crisis. Yet, whilst there are countless texts on wastewater treatment and on membrane technologies, none address the boron problem and separation processes for boron elimination. Boron Separation Processes fills this gap and provides a unique and single source that highlights the growing and competitive importance of these processes. For the first time, the reader is able to see in one reference work the state-of-the-art research in this rapidly growing field. The book focuses on four main areas: Effect of boron on humans and plantsSeparation of boron by ion exchange and adsorption processesSeparation of boron by membrane processesSimulation and optimization studies for boron separation.
Chapter 9 -- Boron Removal From Seawater Using Reverse Osmosis Integrated Processes.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Boron -- Environmental aspects; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Boron -- Environmental aspects; Boron -- Environmental aspects; Boron -- Health aspects; Boron -- Physiological effect; Electronic books; Electronic books